Simultaneous Production Of Bioflocculating Agent And Treatment Of Cibacron Yellow FN-2R By Sphingomonas Paucimobilis Using Sequencing Batch Reactor - Sanayei, Yasaman (2012)
Sphingomonas paucimobilis was found to produce a bioflocculant with high flocculating activity for kaolin suspension and water-soluble dyes. Various culture temperatures (2, 4, 6, 8, 10 hrs) in order to investigate Sphingomonas paucimobilis growth of different culture temperature (30°C, 35°C, 40°C, 45°C) on the bioflocculant production. It was found that flocculating efficiency depends on incubation time and temperature. Highest and lowest production of bioflocculant by Sphingomonas paucimobilis were found at 35°C and 40°C incubation temperature respectively. Two separate experiments, with different range of the dye wastewater concentrations and dosages of Sphingomonas paucimobilis were conducted.